Perception and predication: a synchronic and diachronic analysis of dutch descriptive perception verbs as evidential copular verbs - Poortvliet, M (2018)
Descriptive perception verbs have failed to receive a uniform analysis in previous verb classifications (cf. Chomsky 1965, Rogers 1974, Hengeveld 1992, Levin 1993, Van Eynde et al. 2014). This thesis argues that the descriptive perception verbs in Dutch (i.e. eruitzien ‘look’, klinken ‘sound’, voelen ‘feel’, ruiken ‘smell’, and smaken ‘taste’) should be classified as copular verbs, much like lijken ‘seem’ and schijnen ‘seem’. This classification is supported by both the synchronic and diachronic behaviour of these verbs in Dutch. Synchronically, proposing that Germanic copular verbs (as opposed to copulas) are defined by their syntax rather than their (empty) semantics, I discuss that the Dutch descriptive perception verbs behave like stereotypical copular verbs: they require a predicative complement, usually in the form of an adjective. Semantically, the Dutch descriptive perception verbs are much like the copular verbs blijken ‘turn out’, lijken ‘seem’ and schijnen ‘seem’ in terms of epistemicity and evidentiality. Diachronically, I hypothesize that the Dutch descriptive perception verbs have evolved from one of the following two origins: either from intransitive verbs (as is the case for klinken and ruiken), much like English remain, through grammaticalization processes of semantic bleaching and reanalysis; or from cognitive perception verbs (as is the case of eruitzien and voelen), as found in Latin, Japanese and Zulu, through the process of argument reordering. The origin of smaken is not clear, and is left for future research. I show that other Germanic evidential copular verbs (i.e. lijken, schijnen ‘seem’, scheinen ‘seem’, seem) have developed diachronically in a uniform fashion, suggesting the following grammaticalization path: from a lexical verb to a copular verb, to taking a that-complement, an infinitival complement or a like-complement, and eventually being used in parenthetical constructions. The results of this thesis indicate that the Dutch descriptive perception verbs are only at the beginning of this grammaticalization path, but are on their way to becoming grammaticalized evidential copular verbs.